Pagan Origin of Partialist Doctrines - Pitrat, John Claudius (Auckland : The Floating Press, 2014)
The religious belief of partialism states that not everyone will achieve salvation in God's eyes. Because they subscribe to the notion of hell and eternal damnation, many Christian denominations can be said to hold to the doctrine of partialism. In this book, theologian John Claudius Pitrat contends that this belief system is actually a holdover from pagan times and does not reflect the true nature of Christianity.
Chapter X -- Pagan Origin of the Doctrine of a General Judgment at the End of the WorldChapter XI -- Pagan Origin of the Doctrine of Vicarious Atonement; Conclusion of All the Chapters -- Therefore Partialist Doctrines Are of Pagan Origin; Valedictory.
Print version record.
Keywords: Catholic Church -- Controversial literature -- Protestant authors; Future punishment; Paganism; Universalism; RELIGION -- Christianity -- Orthodox; Electronic books